Identification of Factors Associated with Disease Progression in the Contralateral Hip of Patients with Symptomatic Femoroacetabular Impingement. (139). Issue 10 (31st October 2021) - Khan, Adam; Louer, Craig; Abu-Amer, Wahid; Pashos, Gail; Garrido, Cecilia Pascual; Clohisy, John; Nepple, Jeffrey
Objectives: Femoroacetabular Impingement (FAI) is one of the most common causes of hip osteoarthritis. Nevertheless, the factors contributing to symptom development and FAI disease progression are poorly understood. The purpose of this study was to (1) investigate rates of symptom development in the contralateral hip of patients with FAI at mid-term follow-up, and (2) identify predictors of disease progression (symptom development) in the contralateral hip. Methods: This prospective study included 179 patients undergoing ipsilateral FAI surgery with no history of previous contralateral hip surgery. In the current study, the contralateral hip was assessed at minimum 5 year follow-up. Symptoms (defined as moderate pain) and the need for surgery were monitored over the study course. Statistical analysis compared patient and FAI imaging characteristics of patients developing symptoms to those who remained asymptomatic. Results: A total of 146 hips (81.5%) were included at a mean 6.7 years of follow-up. Thirty-nine (26.7%) presented with symptoms in the contralateral hip, while an additional 35 (23.9%) developed symptoms during the follow-up period. Twenty-Six (17.8%) progressed to surgery for their contralateral hip. Head-neck offset ratio (HNOR) on AP pelvis radiographs was significantly lower among hips that developed symptoms (0.16 vs. 0.15 p=0.03). Maximum alpha angle (p=0.41), lateral center edge angle (p=0.70), and crossover sign (p=0.12) were not predictive of symptoms. Patients with a UCLA activity score greater than 9 were less likely to develop symptoms (14% vs. 46%, p=0.081), but this was not statistically significant. The total arc of rotation in 90° of flexion (40.0° vs 50.8°, p=0.01) as well as external rotation at 90 0 of flexion (28.9° vs 36.6°, p=0.02) were decreased in hips developing symptoms. Internal rotation in flexion was not significantly decreased in symptomatic patients (11.1° vs 14.2°, p=0.11). Kaplan Meier survival analysis demonstrated 53% and 45% of patients remaining asymptomatic at 5 and 8 year time points (Figure). Conclusions: At a mean follow-up of 6.7 years, significant symptoms in the contralateral hip of patients with FAI are present in 50.7% of patients, while 49.3% remain asymptomatic or minimally symptomatic. We identified unique radiographic and physical exam findings that are associated with symptom development in patients with FAI. Specifically, decreased hip rotation arc and decreased HNOR were strongly associated with disease progression and may represent important factors for future risk modeling in FAI patients.